(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: Describe the implementation of the medical assessment process for people with disabilities at the Hanoi Medical Assessment Center in 2023. Methods: Retrospective cross-sectional descriptive study of data conducted on 115 medical examination cases at Hanoi Medical Examination Center in 2023. Results: In most cases of medical assessment, staff receiving documents checked identification documents and information according to regulations (98.3%). Most observations were made by graduate-level examiners (91.3%). The rate of not having a medical examination record recorded in the study was 1.7%. All cases were assigned specialized examinations following the information in the records. The rate of specialist consultation is 99.1%. All observations were attended by a Board of Medical Directors meeting. All 115 councils had all participants. The rate of saving board meeting minutes and documents and issuing minutes according to regulations reached 100%. The average time from receiving the application to the decision and issuance of the minutes is 27.9 days, of which the fastest is 4 days, and the slowest is 231 days. 5/115 of the observed cases of people with disabilities coming to medical clinics complained about the results. Conclusion: Hanoi Medical Assessment Center has complied relatively well with the 8 steps in the medical assessment process for people with disabilities.